C4BPA: A Novel Co-Regulator of Immunity and Fat Metabolism in the Bovine Mammary Epithelial Cells - Iqbal, Ambreen; Ziyi, Pan; Yu, Haibin; Jialing, Li; Haochen, Wu; Jing, Fan; Ping, Jiang; Zhihui, Zhao (Frontiers in Genetics, 2022)
The C4b binding protein alpha (C4BPA) chain primarily engages in critical inflammatory and coagulation processes. The previous transcriptomic analysis showed that C4BPA is a differentially expressed gene in lower and higher fat content mammary gland cell lines from Chinese Holstein. This study aimed to investigate the effects of C4BPA on the inflammation and milk fat synthesis in bMECs by C4BPA knockdown and overexpression. The results highlighted that knockdown of C4BPA in bMECs could suppress the mRNA and protein expression of IL-6, IL-8, IL-12, and the TLR-4/NF-κB pathway-related genes and promote the expression of complement and coagulation cascade pathways related genes as well as TNF-α. Moreover, knockdown of C4BPA expression in bMECs reduced the content of triglyceride (TG) and cholesterol (CHOL) in bMECs, increased NEFA content, reduced mRNA and protein expression of ACSL1 and PPARA, and increased the mRNA and protein expression of ELOVL6, FADS1, and LPL. The bMECs, with the overexpression of C4BPA, showed the enhanced expression of TLR-4/NF-κB linked genes, IL-6, IL-8, IL-12, and mRNA and protein level while reduced mRNA expression of TNF-α, compliment, and coagulation cascade related genes was observed. In bMECs, overexpression of C4BPA enhanced the content of TG and CHOL while reducing NEFA and stimulated the mRNA and protein expression of ACSL1, PPARA, and PPARG genes while inhibiting the mRNA and protein expression of FADS1 and LPL genes. Our results show that C4BPA not only regulates the lipid metabolism through the PPAR signaling pathway in bMECs but also contributes to the inflammatory response through TLR-4/NF-κB and the complement and coagulation cascade pathways. This study, for the first time, provides the primary basis for understanding the role of C4BPA in immunity and fat metabolism, which enables the researchers for innovative direction to investigate genes associated with fat metabolism and immunity. This study also advocates that the breeders must pay attention to such type of genes with multiple functions during animal breeding.